Esercizi di ricerca Dottorato e politiche per la formazione - Boffo, Vanna; Togni, Fabio (Studies on Adult Learning and Education, 2022)
Can research today have a political and a transformative commitment? Can this become the engine of Welfare reforms at all levels and therefore a tool for social change? This collection addresses these and many other questions by collecting a wide variety of studies and research perspectives, while recounting the research paths of the Doctorate in Education and Psychology. The themes and configurations of this Program stands on one of the most promising tracks in the current transformation of Higher Education. Following the Ministerial Decree 226/2021, which has recognized the fundamental role played by PhD students in the building of an integrated Welfare, this volume shows how their work ties in with social needs and social concerns as well as it proposes efficient and effective solutions that are played out within different research fields.